Morfologia e componentes produtivos da soja em arranjos de plantas - Winck, José Eduardo Minussi (2017)
The objective of this project was to characterize the growth, development and productivity of two soybean cultivars of different growth habits in different spatial arrangements of plants and to determine a minimum leaf area index for each plant distribution. Experiments were carried out in the experimental area of the Phytotechnic Department of the Federal University of Santa Maria (29º 43'S, 53º 44 'W), in the agricultural years of 2015/2016 and 2016/2017. The first work consisted of an experiment conducted in a 2x4 factorial scheme, in which the first factor was two cultivars, and the second factor four modes of plant distributions: conventional spacing (spacing of 45 centimeters between rows), reduced spacing (spacing 22.5 centimeters), spacing of pairs (two rows spaced 22.5 centimeters and spaced 45 centimeters from other rows) and cross-spacing (spacing of 45 centimeters between rows with 90 ° angle rows crossing). The second work consisted of 8 experiments for each cultivar, being an experiment for each cultivar in each arrangement of plants in each agricultural year, in a 2x4 factorial, in which the first factor represents two periods of defoliation (R2 and R5), And the second factor the defoliation intensities (0, 33, 67 e 100%). In the two experiments were evaluated characteristics related to growth (leaf area, leaf time life, plastochron and number of nodes), phenology, and productivity componentes. The architecture of the soybean plant is affected by the spacing between rows of sowing, since the arrangement of plants influences the behavior of ecophysiological variables such as plastochron, leaf life time and LAI. The leaf life in each stratum is a result of the foliar senescence rhythm, which is explained by a 4rd order polynomial pattern. Each spacing presents differentiated contributions of each canopy stratum to yield, with wider spacings with a more homogeneous relative production between strata. Due to the plasticity characteristics of the soybean plant, such as the ability to emit branching and increase production on the main stem, the modification in conventional spacing does not yield productivity gains. The indeterminate cultivar has a greater tolerance to leaf area loss in R5 because it has a LAIc (mean of 3.83) lower than the determined cultivar (mean of 4.34). The conventional spacing shows the lowest LAIc in R5 (mean of 3.78). The R5 stage is the most sensitive phenological moment to losses in the productivity components, with the number of pods being the component with the highest productivity compensatory capacity. The flower fixation is up to 70% with accumulated reserves during the growing season, while pods fixation can reach 35% with accumulated reserves until this period.